PDF Towards C+L Band Three-Mode (De)Multiplexer Using Subwavelength Grating (SWG) Technology - Lateef, Zaid; S. Fyath, Raad (Iraqi Journal of Laser, 2022)
Abstract: Recently, there is increasing interest in using mode-division multipelexing (MDM) technique to enhace data rate transmission over multimode fibers. In this technique, each fiber mode is treated as a separate optical carrier to transfer its own data. This paper presents a broadband, compact, and low loss three-mode (de)multiplexer designed for C+L band using subwavelength grating (SWG) technology and built-in silicon-on-insulator SOI platform. SWG offers refractive index engineering for wider operating bandwidth and compact devices compared to conventional ones. The designed (de)multiplex deals with three modes (TE0, TE1, and TE2) and has a loss > -1 dB and crosstalk < −15 dB, and its operation cover 160 nm (1490 to 1650) nm wavelength span. The overall size of the designed device is 80 × 4 μm2.